2022
DOI: 10.1029/2022gl099481
|View full text |Cite
|
Sign up to set email alerts
|

On the Potentials and Limitations of Attributing a Small‐Scale Climate Event

Abstract: A cloudburst is the result of strong convective mechanisms. Due to its intensity, suddenness and brief duration, it is particularly difficult to adequately drain the resulting surface water, which accordingly may lead to severe flooding and consequently large economic losses. Such flash floods are not uncommon across the world and are devastating when occurring in a densely populated city such as Copenhagen, Denmark-even without additional complicating runoff effects from surrounding more elevated areas (Khaje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Initially introduced by Schär et al (1996), this approach investigates how past weather situations might have behaved under future or preindustrial climate conditions, akin to anticipated climate changes (Aalbers et al, 2023;Hawkins et al, 2023). This method has several limitations (inaccuracies in future atmospheric dynamics representations (Rasmussen, 2011;Zhou et al, 2023) and distortions from anomalies in lateral boundary conditions (Matte et al, 2022)) Recent advances have enabled research centers with global models to enhance the study of extreme weather events, including compound events like hot-dry summers (Bevacqua et al, 2023), through large ensembles (Deser et al, 2014), creating diverse climate trajectories by slightly changing initial conditions. Using such ensembles of initialised climate models, it can be assumed that extreme events identified are physically plausibleproviding biases in the model itself are assessed and understood (Thompson et al, 2017;Kelder et al, 2022).…”
Section: State-of-the-art Extremes Modeling Approaches and Gapsmentioning
confidence: 99%
“…Initially introduced by Schär et al (1996), this approach investigates how past weather situations might have behaved under future or preindustrial climate conditions, akin to anticipated climate changes (Aalbers et al, 2023;Hawkins et al, 2023). This method has several limitations (inaccuracies in future atmospheric dynamics representations (Rasmussen, 2011;Zhou et al, 2023) and distortions from anomalies in lateral boundary conditions (Matte et al, 2022)) Recent advances have enabled research centers with global models to enhance the study of extreme weather events, including compound events like hot-dry summers (Bevacqua et al, 2023), through large ensembles (Deser et al, 2014), creating diverse climate trajectories by slightly changing initial conditions. Using such ensembles of initialised climate models, it can be assumed that extreme events identified are physically plausibleproviding biases in the model itself are assessed and understood (Thompson et al, 2017;Kelder et al, 2022).…”
Section: State-of-the-art Extremes Modeling Approaches and Gapsmentioning
confidence: 99%
“…Convective events can occur as a part of frontal systems or as an effect of solar‐heated air becoming more buoyant than the surroundings. A recent attribution study indicates that the observed warming has already increased the risk of extreme precipitation events in Denmark (Matte et al ., 2022). Climate change will increase the occurrence and size of precipitation events and, as a consequence, further increase the risk of pluvial flooding in northern Europe (IPCC, 2021; Christensen et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%